2020
DOI: 10.3390/molecules25040808
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Tumors Using Peptides

Abstract: To penetrate solid tumors, low molecular weight (Mw < 10 KDa) compounds have an edge over antibodies: their higher penetration because of their small size. Because of the dense stroma and high interstitial fluid pressure of solid tumors, the penetration of higher Mw compounds is unfavored and being small thus becomes an advantage. This review covers a wide range of peptidic ligands—linear, cyclic, macrocyclic and cyclotidic peptides—to target tumors: We describe the main tools to identify peptides experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 182 publications
0
40
0
Order By: Relevance
“…[16] Finally, in recent years, other TPP have been described and validated for precision tumor delivery. [9,17,18] Protein/proteins interactions (PPIs) are well recognized as promising therapeutic targets. [19] Given their physicochemical characteristics, interfering peptides (IPs) that modulate PPIs are better suited than small molecules to interfere with the large surface interactions in PPIs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[16] Finally, in recent years, other TPP have been described and validated for precision tumor delivery. [9,17,18] Protein/proteins interactions (PPIs) are well recognized as promising therapeutic targets. [19] Given their physicochemical characteristics, interfering peptides (IPs) that modulate PPIs are better suited than small molecules to interfere with the large surface interactions in PPIs.…”
Section: Introductionmentioning
confidence: 99%
“…[ 16 ] Finally, in recent years, other TPP have been described and validated for precision tumor delivery. [ 9,17,18 ]…”
Section: Introductionmentioning
confidence: 99%
“…Cysteine is known to play a role in structural stability of cyclic peptides through the formation of disulfide bridge [28][29][30][31]. The original CX 7 C phage-displayed peptide library from which the CooP peptide was identified contained two cysteine residues which are important for the stabilization of the peptide structure [2,32]. A previous study showed that adding an extra cysteine residue to a cyclic nonapeptide, iRGD (CRGDK/RGPD/EC), improved the tumor penetrating function [33].…”
Section: Consequently Binding Affinity Measurements Performed By Micmentioning
confidence: 99%
“… 9 SiFA chemistry is a radiofluorination strategy for fast and efficient radiolabeling of higher molecular weight constructs such as peptides, proteins, or nanoparticles that accumulate to tumors by enhanced permeability and retention (EPR) effect 10 , 11 or by targeted strategies. 12 14 Recently, a compound radiolabeled with SiFA chemistry, a somatostatin receptor-2 targeting peptide 18 F-SiFA lin -TATE, has entered clinical trials. 15 17 Main advantage of organophosphine fluoride acceptors or SiFA compounds lie in their tendency to undergo fast isotopic exchange (IE) of fluorine-19 to fluorine-18 ( 19 F/ 18 F), thus generating the 18 F-PET-radiotracer in minutes at ambient temperature.…”
Section: Introductionmentioning
confidence: 99%